2023
DOI: 10.3390/jcm12093161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Teleophthalmology in Delivering Ophthalmic Care to Underserved Populations: A Literature Review

Abstract: Technological advancement has brought commendable changes in medicine, advancing diagnosis, treatment, and interventions. Telemedicine has been adopted by various subspecialties including ophthalmology. Over the years, teleophthalmology has been implemented in various countries, and continuous progress is being made in this area. In underserved populations, due to socioeconomic factors, there is little or no access to healthcare facilities, and people are at higher risk of eye diseases and vision impairment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 117 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…The use of telemedicine has demonstrated its cost-effectiveness and reproducibility not only in ophthalmology but also in other medical specialties. 26 This acceptance of virtual care methods reflects a recognition of their potential to optimize healthcare delivery and improve access to medical services, particularly in times of crisis or when physical visits are limited. 26 Despite the acceptance rate, the predominant type of telemedicine reported was limited to telephone calls for consultations or pre-consultations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of telemedicine has demonstrated its cost-effectiveness and reproducibility not only in ophthalmology but also in other medical specialties. 26 This acceptance of virtual care methods reflects a recognition of their potential to optimize healthcare delivery and improve access to medical services, particularly in times of crisis or when physical visits are limited. 26 Despite the acceptance rate, the predominant type of telemedicine reported was limited to telephone calls for consultations or pre-consultations.…”
Section: Discussionmentioning
confidence: 99%
“… 26 This acceptance of virtual care methods reflects a recognition of their potential to optimize healthcare delivery and improve access to medical services, particularly in times of crisis or when physical visits are limited. 26 Despite the acceptance rate, the predominant type of telemedicine reported was limited to telephone calls for consultations or pre-consultations. On the other side, virtual care tools such as virtual consultations, point-of-care cameras for imaging, virtual waiting rooms, virtual scribes, assisted calls, among others were underutilized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the effectiveness of telemedicine in diabetic eye care, particularly in underserved populations (Aberer et al, 2021;Dolar-Szczasny et al, 2023). Meta-analyses and systematic reviews have consistently shown that telemedicine-based screening programs can improve access to diabetic retinopathy screening and increase the rates of early detection and treatment among underserved populations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also can lead to inter-observer variability, which can further lead to inconsistency in the diagnosis. Also, retinal screening, especially in rural areas, requires specialized equipment and trained medicos, which is again a challenge [10]. Based on these limitations there can be chances that some early-stage retinopathy cases might be missed by current detection methods.…”
Section: Introductionmentioning
confidence: 99%